Patterns of care in patients with muscle-invasive bladder cancer – a retrospective cohort study - Poletajew, Sławomir; Biernacki, Radosław; Buraczyński, Paweł; Chojnacki, Jarosław; Czarniecki, Stefan; Gajewska, Dominika; Pohaba, Tomasz; Sondka, Joanna; Skrzypczyk, Michał; Suchojad, Tomasz; Wojtkowiak, Dominik; Zaforemski, Bogusław; et al. (Contemporary Oncology/Współczesna Onkologia, 2016)
A potential reason for poor survival among patients with muscle-invasive bladder cancer (MIBC) in Poland is initial disqualification from curative treatment due to advanced stage of the disease or low performance status. The aim of this study was to describe patterns of care in patients with newly diagnosed MIBC. This is a multicentre retrospective cohort study involving 296 consecutive patients with primary histologically diagnosed MIBC. Therapeutic decisions and potentially underlying clinical factors were analysed. Full clinical data was available for 285 patients. One hundred and sixty-four (57.5%) patients were qualified for radical cystectomy (RC), 32 (11.2%) patients for a second step of transurethral resection of the bladder tumour (TURBT) intentionally followed by systemic chemotherapy, four (1.4%) patients after complete TURBT were qualified for adjuvant intravesical chemotherapy only, while the remaining 85 (29.8%) patients were qualified for palliative treatment in the form of chemotherapy and/or radiotherapy and/or best supportive care. Patients disqualified from curative treatment were older (78 vs. 69 years, p < 0.02), had lower BMI values (24.5 vs. 25.7 kg/m 2 , p < 0.02), lower haemoglobin concentration (11.6 vs. 12.9 mg/l, p < 0.02), declared lower rate of nicotine abuse (50.5% vs. 72.1%, p < 0.02), and had a shorter time interval between first symptom and diagnosis (30 vs. 60 days, p = 0.02). As the majority of Polish patients with primary MIBC receive curative treatment, the stage of the disease alone seems not to be the leading cause of poor survival. However, appropriateness of qualification for RC and treatment quality needs to be assessed for final conclusion on the factors influencing outcomes of treatment in Poland.